Media Pembelajaran Tangram Pada Materi Bangun Datar Gabungan - Agus Miftakus Surur; Marceria Dwi Cahyani; Azmie Auliyaul Abidah; Rofik Muhzaini; Ahmad Muflih Aminuddin (Faculty of Education and Teacher Training, State Islamic University of Sulthan Thaha Saifuddin Jambi, 2021)
The use of book media and relying on the ability of teachers is something that happens in the field, especially when learning mathematics, so that it can cause problems that are actually common. To overcome this, we need a media to help learning in the classroom. Tangram is one of the media that can be used for learning in the classroom, especially on flat-shaped materials in which there are single and combined shapes. This research is a development research with ADDIE model. The researcher performs the stages of analysis, designing media, developing, testing and reflecting. However, in this study only up to the stage of media development. The results of this media must have been shown to media experts. The result of this research is the formation of a learning media that is ready to be used by students, because it has gone through 3 stages of development, and then implementation. In addition, this media can also be made by students themselves because the steps and procedures for using the media are also available.